Absence of West Antarctic-sourced silt at ODP Site 1096 in the Bellingshausen Sea during the last interglaciation: Support for West Antarctic ice-sheet deglaciation. (1st June 2021) - Carlson, Anders E.; Beard, Brian L.; Hatfield, Robert G.; Laffin, Matthew
Abstract: During the last interglaciation (LIG; ∼129–116 ka), global mean sea level (GMSL) was 6–9 m above present. However, the source, or sources, of the higher-than-present sea level are only partially confirmed with far fewer geologic constraints than GMSL itself. Because of modest LIG Greenland Ice-Sheet retreat that raised sea level by < 2.5 m, Antarctic ice sheets are hypothesized to have contributed significantly to the LIG GMSL highstand, but direct evidence is limited. Here we infer ice-sheet presence or absence on West Antarctica and the Antarctic Peninsula using sediment geochemistry in the Bellingshausen Sea at Ocean Drilling Program (ODP) Site 1096. In particular, a combination of Sr-Nd-Pb isotopes and trace-element ratios allows differentiation between silt sourced from West Antarctica and the Antarctic Peninsula. From the Holocene (<11.7 ka) back through Marine Isotope Stage (MIS) 5d (∼116 ka), we find in ∼50% of our samples glacially eroded silt sourced from under the West Antarctic Ice Sheet that was transported to the Bellingshausen Sea in the Antarctic Circumpolar Current, in addition to silt sourced from under the proximal Antarctic Peninsula Ice Sheet. However, West Antarctic-sourced silt is absent during the LIG (MIS 5e) when only Antarctic Peninsula-sourced silt was deposited at ODP Site 1096. This lack of West Antarctic-sourced silt is consistent with the two ice-core constraints on West Antarctic Ice Sheet LIG size, which combined with our record point towards the absence of the West Antarctic Ice Sheet during the LIG. We therefore provide the first marine-based sedimentary evidence that supports West Antarctic Ice-Sheet absence during the LIG. Highlights: The Bellingshausen Sea contains West Antarctic silt during the last glacial cycle. The Bellingshausen Sea lacks West Antarctic silt during the last interglaciation. West Antarctic last-interglacial deglaciation would explain its silt absence.